The Inclusivism Values of Sheikh Burhanuddin Ulakan's Cultural Preaching as an Alternative to Maintaining National Diversity - Nazirman, Nazirman; Daulay, Zainul; Rais, Zaim; Setiawan, Asep Iwan; Irwandi, Irwandi; Sidik, Mohd Suhadi Mohamed (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2024)
This study aims to describe the values of inclusivism contained by the cultural da'wah model of Sheikh Burhanuddin Ulakan Pariaman as an alternative to caring for national pluralism. The focus of this study is to question what an inclusive da'wah model looks like and how it is implemented, as well as the impact of inclusive da'wah on community culture as a solution alternative in caring for the plurality of nations that live, grow and develop from various ethnicities, religions and beliefs can coexist within the framework of the Unitary State of the Republic of Indonesia. This study examines what values are categorised as inclusivism and how to preserve them in the face of national pluralism. This study uses a literacy review study of various sources concerning the theory of inclusivism in cultural da'wah relations. The findings of this study show that the values carried in Sheikh Burhanuddin's da'wah that are similar to the concept of inclusive da'wah include respecting cultural diversity, making culture an approach and integrating culture with religion, being tolerant and not imposing one's will, and facilitating other people's affairs. The impact of this da'wah is that the Minangkabau people get a basic reference in life which is integrated in the philosophy of adat basandi syarak, syarak basandi kitabullah, syara' mangato adat memakai. This study can be used as an alternative to glue and maintain the integrity of national life in the plurality of nations.